About Calculation and Experimental Estimation of Working Capacity of Ball Joints of a Vehicle Chassis. Part 2. Calculation by Wear Resistance Criterion and Experimental Determination of Characteristics of Wear-Fatigue Damage - Alexander V. Bogdanovich (Механика машин, механизмов и материалов, 2019)
The ball joints of vehicles are referred to the steering and suspension critical units. Strength calculation of the ball pin under static loading is usually performed in the practice of designing these units. In the article, the ball joint is considered as a tribo-fatigue system in which the zones that are dangerous in terms of bending stresses and wear are separated from each other, but are caused by the same load. The necessity of estimating the fatigue resistance of the ball pin and taking into account the uneven distribution of wear over the mating surfaces of the ball head and the liner is shown. The work is done in 2 parts. In the first part, the evaluation of the static and fatigue strength of the ball pin is discussed, and in the second, the assessment of the wear resistance of the joint elements and the proposal for a new method for testing the joint model are considered.